2010
DOI: 10.1111/igc.0b013e3181d66ffe
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing-Related Factor YT521

Abstract: We characterized for the first time in a clinical setting a new but rare exon6-skipping mRNA splicing isoform of YT521. Furthermore, we identified YT521 as a potential new independent prognostic factor for patients with EC: the lack of YT521 protein in tumor cells was highly predictive for a poor overall and disease-specific survival and independent from the histological subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…YTHDC1 represses gene expression by either sequestering splicing factors or directly binding to transcripts [57-59] (Additional file 2: Figure S5A). Among the transcripts that we predict to be potentially targeted by YTHDC1, we found several proto-oncogenes or tumor-associated genes such as RET, PRMT2, RARG and HOXA9 ( RET : interaction propensity = 166; PRMT2 : interaction propensity = 209; RARG : interaction propensity = 194; HOXA9 : interaction propensity = 165; all corresponding to an AUC of 99.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YTHDC1 represses gene expression by either sequestering splicing factors or directly binding to transcripts [57-59] (Additional file 2: Figure S5A). Among the transcripts that we predict to be potentially targeted by YTHDC1, we found several proto-oncogenes or tumor-associated genes such as RET, PRMT2, RARG and HOXA9 ( RET : interaction propensity = 166; PRMT2 : interaction propensity = 209; RARG : interaction propensity = 194; HOXA9 : interaction propensity = 165; all corresponding to an AUC of 99.5%).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that perturbation of the regulation by YTHDC1 of potentially oncogenic genes such as RET, PRMT2, RARG and HOXA9 could be involved in the pathogenesis of related tumors. In fact, experimental studies support the implications for YTHDC1 in cancer progression with regard to angiogenesis, growth factor signaling, immortalization, genetic instability, tissue invasion and apoptosis [59,64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…YTHDC1, the nuclear member of highly conserved YTH family proteins, 100 locates in the nucleus and forms YT bodies at transcriptionally active sites adjacent to RNA processing speckles. 101 Structural and binding studies revealed that YTHDC1 preferentially recognizes the GG(m 6 A)C sequences through its YTH domain. 102 …”
Section: A Readersmentioning
confidence: 99%
“…The YT521 (YTH domain containing 1) is a ubiquitously expressed nuclear splicing factor containing a novel RNA-binding domain (YTH domain) necessary for YT521 to directly influence splice site selection. Importantly, low YT521 expression was associated with clinical outcome in patients with type I endometrial cancer, suggesting its potential role as a tumor suppressor [ 50 ]. Furthermore, YT521 alternative splicing targets are well-known cancer-associated genes such as BRCA2 , ESR1 , MDM2 , VEGF , and CD44 [ 49 , 51 55 ].…”
Section: Alternative Splicing Changes Of Cancer Cells In Response mentioning
confidence: 99%